What is a disappearing intra-abdominal mass? - Ashok Kumar Sahoo; Mangala Goneppanavar; Susan Rajan; Raunak Raj; Vishnu Prasad N R (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Kumar Sahoo A, Goneppanavar M, Rajan S, Raj R, Prasad V. What is a disappearing intra-abdominal mass? Turk J Gastroenterol 2019; 30(9): 843-5.